An odyssey of discovery. Living science - Pierian Spring Software (Firm). (Portland, OR Pierian Spring Software, 1996)
Four activities help users learn about ecology, cells, the nervous system, and heredity. Features three-dimensional graphics, animation, on-screen laboratory notebook, and narrated picture glossary.
The aquarium -- The nerve express -- The private lives of paramecia -- Genes and traits.
Title from disc label.
Ages 9 and up.
Grades 5-8.
System requirements for Windows: 486/66MHz PC; 8MB RAM; Windows 3.1; 20MB free hard disk space; 256-color VGA graphics; 8-bit audio card; 2X CD-ROM drive.
System requirements for Macintosh: 25MHz Macintosh 040; 8MB RAM; System 7.1; 20MB free hard disk space; 13", 256-color monitor; 2X CD-ROM drive.
Keywords: Life sciences -- Juvenile software; Life sciences